The decline in water level and discharge of Lake Toba of North Sumatera, Indonesia, affected by land degradation - Riyanto, Indra Agus; Hendrayana, Heru; Yuli Widyaningsih; Jayanto, Galih Dwi; Azmin Nuha; Sabdo Sumartono (Journal of Degraded and Mining Lands Management, 2025)
Lake Toba is one of the prioritized conservation lakes in Indonesia, crucial for domestic needs, tourism, fisheries, agriculture, and power generation. However, Lake Toba’s water levels and discharge have declined in recent decades. This study aimed to enhance water recharge and the water level of Lake Toba through hydrological modeling using the SWAT analysis and regional and specific conservation measures. The SWAT analysis utilized input data, including climate, soil, geomorphology, land use, and hydrology, to generate both existing and post-conservation water balance models. Conservation methods were categorized into civil engineering and vegetative approaches. Vegetative conservation techniques included agroforestry and MPTS (Multi-Purpose Tree Species), while civil engineering methods encompassed terracing, trenching, and infiltration wells. Regional conservation focused on land use plant types, while specific conservation involved detailed classification of the Lake Toba watershed by slope class, plant type, and land use. The analysis revealed significant land use changes in the Lake Toba catchment area, with dry fields increasing from 72,961 ha to 125,000 ha, a decrease in water level from 905 to 903 m above sea level, and a reduction in discharge from 180 m³/s to 125 m³/s. SWAT analysis shows that the existing inflow to Lake Toba is 131 m³/s (with 78% accuracy), with potential increases to 250 m³/s due to regional conservation and 180 m³/s due to specific conservation. Conservation efforts have also improved discharge rates across 39 sub-watersheds of Lake Toba, both monthly and annually.